Ternary quadratic forms over number fields with small class number - Kirschmer, Markus; Lorch, David (Journal of Number Theory)
We enumerate all positive definite ternary quadratic forms over number fields with class number at most 2. This is done by constructing all definite quaternion orders of type number at most 2 over number fields. Finally, we list all definite quaternion orders of ideal class number 1 or 2.
Keywords: Algebra and Number Theory